Total Life: Jesus’s Surprising Solution for a Health-Conscious World - ACHIM, Ioana (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
In a context that challenges and changes the very definition of personhood, the concept of health itself requires new perspectives. For cancer patients, the desire for health is ubiquitous; therefore, Jesus’s offer of eternal life rather than perpetual health bears significance. The age-long pursuit of health (as typified by the ancient Greek healing cults) and of shalom ‘peace’ (as set forth by the Hebrew Bible and practised by Jesus’s contemporaries) are worthy goals that inspire faith in a higher power and optimism in the face of suffering. However, the persistence of disease, diminishment, and death render such optimism unhelpful. When the loss of health is irretrievable and death approaches, despair and disappointment can set in. Jesus’s promise to Martha of resurrection life both in the hereafter and in the present (enacted on Lazarus and promised to all believers) gives substance to our hope for health and peace. Moreover, the total life that Jesus offers – as opposed to the concept of “total pain” experienced by terminal patients – is based on secure attachment and a higher meaning for any painful experience. As the reader can glean from John 11, Jesus’s interaction with the grieving sisters Mary and Martha opens the window into what God’s presence means in times of unbearable loss. For cancer patients, God’s accompaniment from the moment of diagnosis onward is available in a similar manner: through mirroring, unconditional love, gentle interaction, encouragement to believe, and hope for restoration.